The anacardic acid-loaded nanoliposomes improved the anticancer activity in vitro - Thi Thao, Do; Thi Nga, Nguyen; Thi Phuong, Do; Thi Cuc, Nguyen; Ha Phuong, Trieu; Thi Thu Ha, Dao (Vietnam Journal of Biotechnology, 2023)
Anacardic acid accounts for approximately 77% of the cashew nut shell liquid from Anacardium occidentale, which was reported to have anticancer potential. Due to its water insolubility, the compound is hard to absorb leading to less bioavailability. Currently, using nanolipsomes as drug carriers in general and for anacardic acid in particular could be an effective solution. In this research, anacardic acid was incorporated into nanoliposomes by employing the thin-film method. The results showed that the fabricated nanoliposomes with egg lecithin, cholesterol, and DSPE-PEG as components will have higher encapsulatted efficiency when compared with the fomula using soybean lecithin. The obtained anacardic acid nanoliposomes (AAL) present a size of 135.2 nm, a PDI of 0.095, and a negative zeta voltage of -27.9 mV. The AAL nanoparticles were also evaluated for their growth inhibitory capacity on several cancer cell lines by MTT assay. The GI50 (growth inhibition concentration at 50%) values were determined to range from 80.13 µM to 95.29 µM, of which AAL showed the strongest activity on NTERA-2 human cancer stem cells (80.13 µM). The NTERA-2 cell cycle was also significantly arrested at the S phase (19.43%) under treatment with anacardic acid nanoliposomes. This is the first time for AAL reported activity against cancer stem cells. The activity suggests the potential anti-cancer stem cells of anacardic acid nanolposomes.